Rigiditas dan Fleksibilitas Diskursus Fiqih Wanita Hizbut Tahrir - Umi Chaidaroh (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2017)
Many women in modern times take part in public spaces. Moreover, women are also involved with Islamic movements, which are often associated with fundamentalist movements such as Hizbut Tahrir (HT). In Indonesia, HT has a wing of women’s organization called the Muslimah Hizbut Tahrir Indonesia (MHTI). Women’s activists play a pivotal role in the public space to help HT achieve its goals. Fundamentalist women who work in the public sphere seem to contradict the growing assumption asserting that Islamic fundamentalist movements are often associated with the magnitude of oppression against women. It has been, however, seems to be a paradox. Considering the aforementioned argument, it is important to examine the thoughts concerning women’s jurisprudence of HT. Using a comparative approach, this study focuses on written literature as the main source. The study results prove that the thought concerning women’s jurisprudence of HT tends to be rigid. Interestingly, however, the study also finds that the jurisprudence shows its flexibility within particular cases, but it is even called liberal.